2013
DOI: 10.1517/14656566.2013.808622
|View full text |Cite
|
Sign up to set email alerts
|

Mesalazine for the treatment of inflammatory bowel disease

Abstract: Mesalazine has a well-established role in the management of UC. It is the treatment of choice in active and inactive mild-to-moderate UC combining oral and topical drug. No clear role of mesalazine in prevention of colon cancer has been demonstrated because of the contradictory results coming from case-control and prospective studies. The role of mesalazine in the management of CD is less clear; some studies suggest a potential efficacy of 5-ASA in preventing relapse of CD after surgical resection but more con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…5-ASA also has been shown to activate selective peroxisome proliferator-activated receptor ligand, a nuclear receptor that controls cell proliferation and apoptosis [20]. A specific mode of action cannot be described for 5-ASA and not all of the mechanisms above are beneficiary [20,21]. In our study, 5-ASA showed its most prominent effects in the acute phase of the UC model, it had no effect in the chronic phase, and only decreased the DAI score in the healing phase.…”
Section: Discussionmentioning
confidence: 99%
“…5-ASA also has been shown to activate selective peroxisome proliferator-activated receptor ligand, a nuclear receptor that controls cell proliferation and apoptosis [20]. A specific mode of action cannot be described for 5-ASA and not all of the mechanisms above are beneficiary [20,21]. In our study, 5-ASA showed its most prominent effects in the acute phase of the UC model, it had no effect in the chronic phase, and only decreased the DAI score in the healing phase.…”
Section: Discussionmentioning
confidence: 99%
“…Mesalazine, also known as 5-aminosalicylic acid (5-ASA), has been used for over 40 years as the first-line treatment for mild to moderate ulcerative colitis. [89][90][91] 5-ASA acts predominantly topical at the site of inflammation, especially within the colon, [92][93][94] presumably by activating PPAR-γ-signaling in colonocytes. 95 Since PPAR-γ-signaling is a strong driver of βoxidation in colonocytes 73 (Fig.…”
Section: Healthy Guts Exclude Oxygen: How the Host Controls Its Colonmentioning
confidence: 99%
“…20) Accordingly, the investigation of pH responsive and/or colon targeted formulations for 5-ASA was utilized in the clinical practice. 20,21) Thus, in case utilizing the modified release 5-ASA formulation in clinical practice, colonic concentration of 5-ASA must be higher, suggesting the inhibitory effect of 5-ASA on PEPT1 would be more effective. Still, however, it hardly seems difficult that almost complete inhibition for PepT1-mediated transport by 5-ASA would occur.…”
Section: -17)mentioning
confidence: 99%